PENGARUH PEMANFAATAN MUSEUM MPU TANTULAR SEBAGAI SUMBER BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X IPS 4 PADA MATERI PERKEMBANGAN MASYARAKAT PADA MASA HINDU-BUDHA DI INDONESIA DI SMA MUHAMMADIYAH 2 SIDOARJO - wicaksana, wahyu endra (The Indonesian Journal of Social Studies, 2018)
AbstractAlong with the increasing need to provide better teaching, also increased use of methods in providing materials to trainees. One of the methods currently considered as an interesting method is to utilize learning resources to facilitate the delivery of materials where the methods that are deemed relevant to IPS subjects are museums. The purpose of this research is to analyze the effect of MpuTantular Museum Utilization as a learning resource to the learning outcomes of the students of class X IPS 4 SMA Muhammadiyah 2 Sidoarjo on the material of "the development of society during Hindu Buddhism" and the difference of the students' learning result using the learning resources Museum with students whose learning using textbooks on the students of class X IPS in SMA Muhammadiyah 2 Sidoarjo. This study uses quasi experiment because it uses existing classes. The results of this study are there are differences of students who use the Museum learning resources with students who use textbooks because there are differences in treatment between the control class and experimental class. The sample of this research is the students of class X IPS 5 as the control class and the students of class X IPS 4 are experiment class. Improved better learning outcomes are shown in the experimental class, ie the average score of post test class test results is 33.68 while the control class average is 25.78. The result of t-test is t = 7,694>ttable = 2,026 which means that there can be significant difference, that is experiment class learning result better than control class.Keywords: Museum Utilization, Historical Learning Resources, Learning Outcomes